A Knowledge-Based E-mail System Using Semantic Categorization and Rating Mechanisms. - Mohd Kassim, Azleena; A. Rahman, Muhamad Rashidi; Cheah, Yu N (2008)

(untitled)
Knowledge-based e-mail systems focus on incorporating knowledge management approach in order to enhance the traditional e-mail systems. In this paper, we present a Knowledge-based e-mail systems called KS-Mail where people do not only send and receive e-mail conventionally but are also able to create a sense of knowledge flow. We introduce semantic processing on the e-mail contents by automatically assigning categories and providing links to semantically related e-mails.